A case report on anti-epileptic drugs associated cerebral palsy and rickets - Behera, Sunil K.; Amaravadi, Divya; Suman, Gurnoor; Hala, N. Shri; Shreya, Arvini (International Journal of Contemporary Pediatrics, 2023)
Seizures are incredibly widespread all around the world, today. A seizure is often described as a transient alteration in the electrical activity of the brain. This required the treatment with antiepileptic drugs (AEDs). The majority of AEDs lower vitamin D levels. Vitamin D is found to be crucial for intestinal absorption of calcium, magnesium, and phosphate which helps to build and mineralize bones. Vitamin D deficiency has been seen to be a causative reason for cerebral palsy which is a neurological illness that affects movement and muscle coordination, permanently. It has been observed to manifest in infancy or early childhood due to vitamin D deficiency due to long term use of AEDs making it severe due to malnourishment. This case reports the use of antiepileptic drugs leading to cerebral palsy due to vitamin D deficiency. Therefore, by this case report we want to alert the readers and healthcare professionals about the possible adverse effects of AEDs and to be aware of them.